Podpora staršem ob izgubi kritično bolnih otrok v enotah intenzivne zdravstene nege in terapije - Baznik, Simona (Obzornik zdravstvene nege, 2005)
The article deals with experiences of parents and critically ill children on intensive care units. ln the literature survey, critically ill children and their parents are being followed during their stay in the intensive care unit,at the moment when the parents learn that their child is going to die andat death itself. The purpose of the literature survey was to improve the quality of active attendance to the parents of critically ill and dying children in intensive care units, as well as to be able to form propositions for better ractice and for staff education. The article also describes fears and feeling of failure the parents are confronted with when death of their child becomes imminent, as well as the work of nurses and other health professionals in intensive are units. Care theory of Jean Watson was used. In the end ie author gives advice to health workers regarding their eactions whena child dies, and forms proposition for qualitative attendance to the parents when their child dies and during the mourning process.
Keywords: Bereavement; bolniki; Child; Critical Illness; death; Intensive Care Units, Pediatric; intenzivna nega; Intenzivna oskrba, enote pediatrične; Kritična bolezen; Medicinska sestra-bolnik, odnosi; Nurse-Patient Relations; otroci; Otrok; Parents; smrt; Starši; Žalovanje